Community Based Essential Newborn Care Practices and Associated Factors among Women Who Gave Birth at Home in Last 12 Months in Amaro Woreda, Southern Ethiopia, 2019 - Mamush Agonafir MPH; Mulugeta Shegaze Shimbre MPH; Sultan Hussen MPH; Gebremaryam Temesgen MSc; Belay Boday MSc; Abayneh Tunje MPH; Teshale Fikadu MPH; Eshetu Andarge MPH; Yaregal Fufa MD, MPH; Yeabsira Gebrewold MSc (SAGE Publishing, 2021)
Community based newborn care is a means of bringing life-saving care to mothers and newborns at the community level. However, the practice is challenging within the Ethiopian health system. The aim of this study was to assess prevalence of community based newborn care practices and associated factors among women who gave birth at home in Amaro Woreda, southern Ethiopia, 2019. Across-sectional study design and simple random sampling technique was employed to select study participants. Data was collected through face-to-face interview; EpiData version 3.1 and SPSS version 20 software were used for analysis. Bi-variable and multivariable logistic regression was employed to analyze the associated factors. In this study 29% practiced community based essential newborn care. Educational status of father (AOR = 2.28; 95% CI: 1.07-4.84), last delivery assisted by relative (AOR = 3.58; 95% CI: 1.66-7.73), having awareness about community based newborn care (AOR = 3.49; 95% CI: 2.11-5.77), awareness about newborn danger sign (AOR = 2.18; 95% CI: 1.29-3.68) were some of identified factors associated with community based newborn care practice. In conclusion, community based newborn care practice was low. Therefore, promotion of information at community level, women empowerment, and strengthening health extension program were recommending.